Beliefs, practices, and advice received on nutrition and health during pregnancy: Qualitative reports from pregnant women in rural Bangladesh (P10-021-19) - Nath, Preyanka; Byrd, Kendra; Das, Jyoti; Sharmin, Afsana; Amin, Ruhul; Rahman, Mahbubar; Mridha, Malay (Oxford Academic, 2022)
This article was published in the Current Developments in Nutrition [Copyright © American Society for Nutrition 2019. This article is published and distributed under the terms of the Oxford University Press, Standard Journals Publication Model (https://academic.oup.com/journals/pages/open_access/funder_policies/chorus/standard_publication_model)] and the definite version is available at: https://doi.org/10.1093/cdn/nzz034.P10-021-19 The Journal's website is at: https://academic.oup.com/cdn/article/3/Supplement_1/nzz034.P10-021-19/5517042